NEW MARKER PERFORMING THE EFFICIENCY OF CORRECTION OF MOVEMENT PATTERNS IN PATIENTS WITH SPASTIC FORMS OF CEREBRAL PALSY - Strashko, E.Y. (World of Medicine and Biology, 2012)
The article provides a scientific justification of use of a new marker performing the efficiency of correction of movement patterns in patients with spastic forms of cerebral palsy by evaluating the range of motion in the cervical spine as an element of spiral muscle, evaluating the intensity of pain. Rehabilitation program proposed by the author provides impact on cerebral palsy with the involvement of all biokinetic muscle chains, considering spiral composition of body muscles during rehabilitation procedures. Increase of range of motion in cervical spine area considering the intensity of pain should be used as a performance criterion of rehabilitation effects on spiral muscle in patients with spastic form of cerebral palsy.
Keywords: cerebral palsy; muscular spiral; cervical area of the spine; rehabilitation; motor stereotype